DEVELOPING TOLERANT THINKING IN PRE-SERVICE ENGLISH LANGUAGE TEACHERS THROUGH SOFT SKILLS-BASED PEDAGOGICAL TECHNOLOGIES (SCIENCE TIME JOURNAL, 2026)
This research investigates how soft skills-based teaching technologies help pre-service English teachers develop their capacity to think with tolerance. The research examines current teaching technologies which help future educators develop tolerant attitudes and critical thinking skills and empathetic abilities and intercultural understanding. The study results show that soft skills-based methods which include collaborative learning and reflective practice and intercultural communication training help develop tolerant attitudes in future English language teachers.